2005
DOI: 10.1152/ajpheart.01053.2004
|View full text |Cite
|
Sign up to set email alerts
|

Reduced functional expression of K+channels in vascular smooth muscle cells from rats made hypertensive withNω-nitro-l-arginine

Abstract: , we demonstrated that superior mesenteric arteries from rats made hypertensive with N -nitro-L-arginine (L-NNA) are depolarized and express less K ϩ channel protein compared with those from normotensive rats. In the present study, we used patch-clamp techniques to test the hypothesis that L-NNA-induced hypertension reduces the functional expression of K ϩ channels in smooth muscle. In whole cell experiments using a Ca 2ϩ -free pipette solution, current at 0 mV, largely due to voltage-dependent K ϩ (KV) channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 44 publications
5
29
0
Order By: Relevance
“…The mechanism that regulates K v channel expression and BK Ca channel expression in SHRs is very complicated and is poorly understood because the differential expression of these channels has been observed in various arteries [6,16]. The loss of K v channels can be considered a factor that contributes to augmented vessel force [23]. β1-subunits of BK Ca promote the function of the channels through increasing Ca 2± and voltage sensitivity; thus, the upregulation of β1-subunit in hypertension could be considered a mechanism that suppresses augmented vessel force in hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism that regulates K v channel expression and BK Ca channel expression in SHRs is very complicated and is poorly understood because the differential expression of these channels has been observed in various arteries [6,16]. The loss of K v channels can be considered a factor that contributes to augmented vessel force [23]. β1-subunits of BK Ca promote the function of the channels through increasing Ca 2± and voltage sensitivity; thus, the upregulation of β1-subunit in hypertension could be considered a mechanism that suppresses augmented vessel force in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the role of the K v and BK Ca channel on modulating vascular tone, the ring-like aortas were treated with 4-aminopyridine (4-AP, 3 m M ), tetraethylammonium (TEA, 1 m M ), Maurotoxin (MTX, 30 n M ), and Mephetyl tetrazole (MEP, 10 μ M ). 4-AP is a potent K v channel blocker [4] and TEA at ≤1 m M can inhibit BK Ca channel but has little effect on K v channels [23,24,25]. In order to specifically target K v 1.2 and K v 1.5, the ring segments were treated with their respective blockers, MTX and MEP [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a reduction in BK currents has been reported by others in myocytes from SHRs 32 and angiotensin II-induced, 33 and N -nitro-L-arginine-induced hypertensive rats 30,31 with or without the reduction of expression of BK channel ␣-subunits. The studies of Amberg and colleagues 32,33 demonstrate a reduc- tion in BK current secondary to diminished expression of the regulatory ␤1-subunit in SHR and angiotensin II-induced hypertension without a change in expression of ␣-subunits.…”
Section: Xu Et Al Tempol Activates Bk Channels In Myocytesmentioning
confidence: 84%
“…Other studies in N -nitro-L-arginine-induced hypertensive rats demonstrated that there was a reduced BK channel ␣-subunit expression and BK current but no difference in the Ca 2ϩ /voltage sensitivity of BK channels. 30,31 These data suggest that the effect of hypertension on BK channel expression may be model dependent. .…”
Section: Xu Et Al Tempol Activates Bk Channels In Myocytesmentioning
confidence: 88%
See 1 more Smart Citation